Quantifying how smokers value attributes of electronic cigarettes. Issue Volume 25:Issue e1(2016) (6th November 2015) - Nonnemaker, James; Kim, Annice E; Lee, Youn Ok; MacMonegle, Anna
Abstract : Introduction: Rates of electronic cigarette (e-cigarette) use have increased quickly among US adults (3.3% in 2010 to 8.5% in 2013) and youth (4.5% in 2013 to 13.4% in 2014). As state and local governments consider regulatory policies, understanding what smokers believe about e-cigarettes and how they value e-cigarettes is important. Methods: Using data from a convenience sample of Florida adult smokers (N=765), we investigated the value smokers place on specific attributes of e-cigarettes (availability of flavours, effectiveness of e-cigarettes as a cessation aid, healthier alternative to regular cigarettes, ability to use e-cigarettes in public places) by asking smokers how much they would be willing to pay for e-cigarettes with and without each of these attributes. Results: For cigarette-only and dual users, losing the ability to use an e-cigarette as a quit aid and losing the harm reduction of an e-cigarette significantly reduced the price respondents were willing to pay for an e-cigarette. For cigarette-only users, not being able to use an e-cigarette indoors and losing flavours also significantly reduced the price respondents were willing to pay for an e-cigarette. Conclusion: Our results suggest that smokers value multiple attributes of e-cigarettes. Our valuation measures also appear to align with smokers' beliefs about e-cigarettes.